2010
DOI: 10.1097/yic.0b013e32833e23ed
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic study of changes in pharmacological prescription for borderline personality disorder in clinical practice: from APA to NICE guidelines

Abstract: Although no psychotropic agents are specifically licensed for the management of borderline personality disorder (BPD), pharmacological treatment appears to be common. This study aimed to examine the drug prescriptions for patients with BPD in clinical practice, analyze the prescription patterns from the appearance of the American Psychiatric Association guidelines in 2001 until the National Institute for Health and Clinical Excellence guidelines in 2009, and identify the factors associated with such prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
2
26
1
3
Order By: Relevance
“…1 In our subgroup of patients with EUPD alone, threequarters were prescribed an antidepressant; three-fifths, an antipsychotic drug; one-third, a benzodiazepine; and onefifth, a z-hypnotic or mood stabilizer. The high prevalence of antidepressant use is consistent with other surveys of prescribing practice [8][9][10] but in contrast with the findings from clinical studies that these drugs are not effective in treating affective symptoms in patients with EUPD 17 and are relatively less effective in treating depression in people with comorbid personality disorder than in those without. 19,20 A higher proportion of our patients with EUPD were prescribed an antipsychotic than the 40% reported by Pascual et al 8 in a naturalistic study of 226 consecutive patients with BPD admitted to an outpatient program, although these investigators noted an increasing prevalence of antipsychotic prescribing over time.…”
Section: High Prevalence Of Psychotropic Drug Prescribing For Eupdcontrasting
confidence: 49%
See 2 more Smart Citations
“…1 In our subgroup of patients with EUPD alone, threequarters were prescribed an antidepressant; three-fifths, an antipsychotic drug; one-third, a benzodiazepine; and onefifth, a z-hypnotic or mood stabilizer. The high prevalence of antidepressant use is consistent with other surveys of prescribing practice [8][9][10] but in contrast with the findings from clinical studies that these drugs are not effective in treating affective symptoms in patients with EUPD 17 and are relatively less effective in treating depression in people with comorbid personality disorder than in those without. 19,20 A higher proportion of our patients with EUPD were prescribed an antipsychotic than the 40% reported by Pascual et al 8 in a naturalistic study of 226 consecutive patients with BPD admitted to an outpatient program, although these investigators noted an increasing prevalence of antipsychotic prescribing over time.…”
Section: High Prevalence Of Psychotropic Drug Prescribing For Eupdcontrasting
confidence: 49%
“…5,[7][8][9] Polypharmacy was also common with two-thirds of patients with EUPD alone prescribed psychotropic drugs from at least 2 different classes and almost a fifth from at least 4. This is consistent with Zanarini et al, 6 who reported that 11% of those with EUPD were taking 5 or more psychotropic drugs, although these investigators included patients with comorbid mental illness.…”
Section: High Prevalence Of Psychotropic Drug Prescribing For Eupdmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the elevated and increasing worldwide prevalence of neuropsychiatric disorders (10% of adults, according to an 2006 estimation of the World Health Organization (Albrecht, 2006)) the use of antipsychotic drugs has expanded dramatically over the last decade (Alessi-Severini et al, 2012;Bulloch et al, 2012;Comer et al, 2011;Pascual et al, 2010). This increase was also potentiated by the introduction of "second generation" or atypical antipsychotics such as quetiapine, risperidone, olanzapine, clozapine and aripiprazole (Kessler et al, 2003), which in contrast to "first generation" or typical antipsychotics, have a higher clinical efficacy and a lower risk of inducing adverse extrapyramidal symptoms (movement disorders) (Monshat et al, 2010;Shah et al, 2011).…”
Section: Antipsychotic Drugsmentioning
confidence: 99%
“…Not only is there insufficient evidence regarding which treatments may be most effective, 9,20 but it is virtually impossible to prevent patients from harming themselves through the ingestion of objects. Current consensus emphasizes the importance of forming a supportive and collaborative therapeutic alliance, validating the patient's feelings, conducting functional analyses of the self-harming episodes, managing reinforcement contingencies, and teaching new skills such as problem-solving or distress tolerance.…”
Section: Discussionmentioning
confidence: 99%